The impact of climate change on health expenditures - Ivan Frankovic (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
We study the effect of climate-induced health risks within a continuous time OLG economy with a realistic demography and endogenous mortality. Climate change impacts the economy through two channels. First, a degrading environmental quality increases mortality, affecting the demand for health care. Second, production losses are caused through deteriorating climate conditions and lead to reductions in income. We explore how individuals respond to these climate change impacts with respect to their life-cycle decisions and assess the overall effect on aggregate health care demand. We put special focus on age-specific vulnerabilities of climateinduced health risks and explore the response to climate change across age-groups. We solve the model numerically and show that health care demand is subject to two opposing forces. While climate-induced mortality increases demand for medical care, reduced income tends to lower health spending, particularly among the elderly. Moreover, we find that age-specific vulnerabilities to climate change considerably shape the effect on aggregate health care demand. Our analysis, thus, highlights the important role of a full life-cycle perspective in the estimation of climate-induced health costs.
Keywords: D91; I12; I15; J11; J17; Q54; 330; climate change; climate-induced health risks; life-cycle model; health care; value of life